PROSES INDUSTRIALISASI DI INDONESIA DALAM PRESPEKTIF EKONOMI POLITIK - Damayanthi, Vivin Retno (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
Industrialization has become one of the economic transformation programs inIndonesia. There are many policies implemented to support the programs. This paperwill observe the process of industrialization in Indonesia in the perspective of politicaleconomy. Furthermore, it also will analyze on how economic policy will support theindustrial sector in Indonesia and its role on economic growth.Keywords: Industrialization, Political Economy and Economic Policy